2016
DOI: 10.1111/cts.12383
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Nongenetic Factors Affecting Clopidogrel Response in the Egyptian Population

Abstract: Aspirin and clopidogrel are the mainstay oral antiplatelet regimens, yet a substantial number of major adverse cardiac events (MACE) still occur. Herein, we investigated genetic and nongenetic factors associated with clopidogrel response in Egyptians. In all, 190 Egyptians with acute coronary syndrome (ACS) and/or percutaneous coronary intervention (PCI), treated with clopidogrel (75 mg/day) for at least a month, were genotyped for CYP2C19 *2, *3, *6, *8, *10, and *17, CES1 G143E and ABCB1*6 and *8. These vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…A systematic review and meta-analysis by Bauer et al (2011) revealed no substantial or consistent influence of CYP2C19 variants on the clinical efficacy of clopidogrel and risk of MACE. In contrast, the groups of Mega and Han reported significantly increased risk of MACE in association with CYP2C19 * 2 and * 3 variants (Mega et al, 2010b; Han et al, 2015; Khalil et al, 2016). …”
Section: Introductionmentioning
confidence: 92%
“…A systematic review and meta-analysis by Bauer et al (2011) revealed no substantial or consistent influence of CYP2C19 variants on the clinical efficacy of clopidogrel and risk of MACE. In contrast, the groups of Mega and Han reported significantly increased risk of MACE in association with CYP2C19 * 2 and * 3 variants (Mega et al, 2010b; Han et al, 2015; Khalil et al, 2016). …”
Section: Introductionmentioning
confidence: 92%
“…In recent years, the focus of pharmacogenomics research has evolved from the traditional emphasis on discovering genetic determinants of drug exposure (pharmacokinetics), to a broader definition that includes genes and pathways that underlie the pharmacologic and toxic response to therapeutics (pharmacodynamics). In this issue, Khalil et al . and Hamadeh et al .…”
Section: Example Topics Of Interest For Clinical and Translational Scmentioning
confidence: 95%
“…Age and BMI were significantly associated with clopidogrel response [75,76]. Older age was independently associated with a higher rate of high residual on-treatment platelet reactivity with both clopidogrel and ticagrelor in 494 patients on dual antiplatelet therapy [77].…”
Section: Non-genetic Factors Influencing Clopidogrel Responsementioning
confidence: 99%